Networks of Knowledge: Two Canadian Scientists and their Transborder Contacts - Hull, James (Scientia Canadensis, 1991)
ABSTRACTRecently published letters of Dr Karl A. Clark, who worked from 1920 to 1949 on the hot water separation process for extracting petroleum from the Athabasca oil sands, and records of Dr Clara W. Fritz, who, in the 1930s, examined the problem of pulp mill slime which weakened and discoloured paper products offer insights into how Canadian scientists worked in an international network of scientists. What were the roles played by these scientists in managing the international flow of scientific knowledge? How did they work? Who were their contacts? What were the institutional foci of their work? In answering these questions, we will come to a better understanding of the Canadian scientific infrastructure during this crucial period.